Incipient silicification of recent conifer wood at a Yellowstone hot spring. (15th January 2015) - Hellawell, Jo; Ballhaus, Chris; Gee, Carole T.; Mustoe, George E.; Nagel, Thorsten J.; Wirth, Richard; Rethemeyer, Janet; Tomaschek, Frank; Geisler, Thorsten; Greef, Karin; Mansfeldt, Tim
Abstract: A branch of lodgepole pine ( Pinus contorta ) from a silica sinter apron of Cistern Spring, Yellowstone National Park, is partially mineralized with silica gel. The distribution of Si mapped in transverse sections of the branch suggests that mineralization was episodic. Early silica-rich solutions used the cellular structures in the wood as pathways, in particular the axial tracheids and rays. Later solutions infiltrated into the branch through shrinkage cracks along the decorticated branch's periphery. Among the tracheids, a distinct preference is noted for silica precipitates to line lumina of the earlywood tracheids, suggesting that this differential concentration in silica may reflect seasonal growth and water uptake in a live tree. Raman spectroscopy identifies the silica phases as amorphous silica gel. Secondary electron images of radial sections along the tracheids demonstrate that the distribution of silica is heterogeneous on a micrometer scale. Silica gel precipitates form micro spheroids with a spherical substructure that extends down to the sub-nanometer scale. All cell walls are templated with a monolayer consisting of closely spaced silica gel nano spheres around 100 nm in diameter. Transmission electron microscopy of focused ion beam sections through cell walls of partially mineralized tracheids reveals that the permineralization of cellular structures and the replacement of organic material by silica are processes that go hand in hand. The branch is dated with the 14 C chronometer to 140 ± 33 years, underlining that the silicification reactions that preserve wood in the fossil record can be very rapid. Textural considerations of Si distribution in the wood suggest that the early stages of silicification in this branch date from a time when the pine tree was still alive.